2005
DOI: 10.1143/jjap.44.8125
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Two Phases of Neutron Emission in a Low Energy Plasma Focus

Abstract: Nonrepeatability in measured values of the static breakdown voltage Vs of uniform-field high-pressure gas-discharge gaps necessitates a large number of measurements to be made in order to construct meaningful V, distribution curves. An apparatus has been constructed which is capable of automatic measurement and recording of breakdown voltage data. This enables results to be obtained under more precise conditions than are possible using normal experimental techniques. The design and performance of this system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…This particular setup offers exceptionally low jitter (on the order of ns) and sensitivity to single particles [30]. Having many of these independent detectors opens up a tremendous array of possible measurements including: time-of-flight (TOF) measurements, angular distribution of neutrons (the yield of DPFs is known to be anisotropic [27]), temporal distribution of neutron production (as in [23,27]).…”
Section: Radiation Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…This particular setup offers exceptionally low jitter (on the order of ns) and sensitivity to single particles [30]. Having many of these independent detectors opens up a tremendous array of possible measurements including: time-of-flight (TOF) measurements, angular distribution of neutrons (the yield of DPFs is known to be anisotropic [27]), temporal distribution of neutron production (as in [23,27]).…”
Section: Radiation Diagnosticsmentioning
confidence: 99%
“…Running DPFs with an admixture of deuterium and a heavy noble gas has been tested by several research groups, with DPF energies ranging from 100's of Joules to 100's of kJ. The results have varied significantly with some groups reporting enhancements under optimal conditions in excess of 30× and other groups reporting reduced yields compared to pure deuterium [23][24][25][26][27][28]. Our system was the first used to test such piston gases in a 100 J-class DPF.…”
Section: Noble Gas Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bernstein suggested that the experimental observed neutron emission was inconsistent with the thermonuclear assumption [9]. Abundance of results later also showed non-thermonuclear origin in the neutron emission [10][11][12]. A research group even reported that the presence of anisotropy in the neutron emission could not be interpreted solely by any single proposed model [13].…”
Section: Introductionmentioning
confidence: 99%
“…The plasma produced is of very high temperature (1-3 keV) and high density (>10 19 Particles/cm 3 ) [1]. The device is particularly interesting due to its special characteristic as intense pulsed sources of X-rays, ions, electrons and neutrons (deuterium filling) [2][3][4][5]. The early research was concentrated on the neutron emission [6,7] and yet in recent years, there is abrupt growth of researcher's interest in utilized plasma focus for its application in surface modification [8], ion implantation [9] and thin film deposition [10].…”
Section: Introductionmentioning
confidence: 99%